The Levittowners : Ways of Life and Politics in a New Suburban Community - Gans, Herbert J.; Molotch, Harvey (New York, NY : Columbia University Press, 2018)
In 1955, Levitt and Sons purchased most of Willingboro Township, New Jersey and built 11,000 homes. This, their third Levittown, became the site of one of urban sociology's most famous community studies, Herbert J. Gans's The Levittowners. The product of two years of living in Levittown, the work chronicles the invention of a new community and its major institutions, the beginnings of social and political life, and the former city residents' adaptation to suburban living. Gans uses his research to reject the charge that suburbs are sterile and pathological. First published in 1967, The Levittowners is a classic of participant-observer ethnography that also paints a sensitive portrait of working-class and lower-middle-class life in America. This new edition features a foreword by Harvey Molotch that reflects on Gans's challenges to conventional wisdom.
Frontmatter -- Contents -- List of Tables -- Foreword / Molotch, Harvey -- Preface to the Morningside Edition -- Preface -- Acknowledgments -- Introduction. The Setting, Theory, and Method of the Study -- Part 1 - THE ORIGIN OF A COMMUNITY -- One. The Planners of Levittown -- Two. The Levittowners and Why They Came -- Three. The Beginnings of Group Life -- Four. The Founding of Churches -- Five. The New School System -- Six. The Emergence of Party Politics -- Seven. The Origin of a Community -- PART 2 THE QUALITY OF SUBURBAN LIFE -- Eight. Social Life: Suburban Homogeneity and Conformity -- Nine. The Vitality of Community Culture -- Ten. Family and Individual Adaptation -- Eleven. The Impact of the Community -- PART 3 THE DEMOCRACY OF POLITICS -- Twelve. Political Communication -- Thirteen. The Decision- making Process -- Fourteen. Politics and Planning -- Fifteen. Levittown and America -- Appendix. The Methods of the Study -- References -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Sep 2018)
Keywords: Suburban life